Combination of β-Aminobutyric Acid and Ca2+ Alleviates Chilling Stress in Tobacco (Nicotiana tabacum L.) - Ma, Xiao-Han; Xu, Jia-Yang; Han, Dan; Huang, Wu-Xing; Dang, Bing-Jun; Jia, Wei; Xu, Zi-Cheng (Frontiers in Plant Science, 2020)
Chilling is a major abiotic factor limiting the growth, development, and productivity of plants. β-aminobutyric acid (BABA), a new environmentally friendly agent, is widely used to induce plant resistance to biotic and abiotic stress. Calcium, as a signaling substance, participates in various physiological activities in cells and plays a positive role in plant defense against cold conditions. In this study, we used tobacco as a model plant to determine whether BABA could alleviate chilling stress and further to explore the relationship between BABA and Ca2+. The results showed that 0.2 mM BABA significantly reduced the damage to tobacco seedlings from chilling stress, as evidenced by an increase in photosynthetic pigments, the maintenance of cell structure, and upregulated expression of NtLDC1, NtERD10B, and NtERD10D. Furthermore, 0.2 mM BABA combined with 10 mM Ca2+ increased the fresh and dry weights of both roots and shoots markedly. Compared to that with single BABA treatment, adding Ca2+ reduced cold injury to the plant cell membrane, decreased ROS production, and increased antioxidant enzyme activities and antioxidant contents. The combination of BABA and Ca2+ also improved abscisic acid and auxin contents in tobacco seedlings under chilling stress, whereas ethylene glycol-bis (β-aminoethylether)-N,N,N’,N’-tetraacetic acid (EGTA) reversed the effects of BABA. These findings suggested that BABA enhances the cold tolerance of tobacco and is closely related to the state of Ca2+ signaling.